2013
DOI: 10.24191/jeeir.v1i3.9128
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic and Bank Specific Covariates of Non-Performing Loans (NPLs) in Pakistani Commercial Banks: Panel Data Evidence

Abstract: Non-performing loans has become an important part of commercial banking of a country. This paper empirically tests the macroeconomic and bank-specific covariates of non-performing loans for a panel of 13 commercial banks for period of 2003-2012. Using fixed effects with Driscoll and Kraay standard errors, the influence of macroeconomic and bank-specific covariates is found meaningful. Recommendations include the policy steps to complement the sound financial system with a healthy macroeconomic environment to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Banking data are retrieved from balance sheets and income statements of the individual banks. Nine different types of banks are used for analysis from the time period ranging from (Badar and Yasmin Javid, 2013;Mehmood et al, 2013;Jameel, 2014). Studies on assessing NPLs considering data from recent years are lacking.…”
Section: Methodsmentioning
confidence: 99%
“…Banking data are retrieved from balance sheets and income statements of the individual banks. Nine different types of banks are used for analysis from the time period ranging from (Badar and Yasmin Javid, 2013;Mehmood et al, 2013;Jameel, 2014). Studies on assessing NPLs considering data from recent years are lacking.…”
Section: Methodsmentioning
confidence: 99%
“…Floating interest rates also affect NPLs as higher interest rates tend to lead to a higher difficulty of borrowers to repay their debt obligations. Many studies showed that interest rates possess a significant positive effect with NPLs, where debt amount increases as interest rates increase, resulting in a rise in NPLs (Erdo gdu, 2016;Mehmood et al, 2013;Bofondi and Ropele, 2011;Rinaldi, 2006;Fofack, 2005;Khemraj and Pasha, 2009;Jimenez and Saurina, 2006). Many of the previous empirical studies showed that interest rate had IJHMA 15,5 been significant in affecting NPLs, despite the passage of different macroeconomic environments.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, authors' recommendations imply creating a healthy macroeconomic environment in order to reduce level of non-performing loans in Pakistan commercial banks. The emphasis is also on adequate credit culture and lending policy designed in accordance with appropriate economical and financial factors (Mehamood et. al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%